Dom Hélvecio Gomes de Oliveira, um salesiano no episcopado: artífice da neocristandade (1888-1952) - Mabel Salgado Pereira (2010)
This work is dedicated to the historical study of the religious HelvecioGomes de Oliveiras trajectory, member of the St. Francis de Sales Association, and his actions inside the Catholic Church, from 1888 to1952. The religious developed a significant role in the Brazilian Catholicisms dimension, especially in the movement known as neo-Christianity, in other words, the approximation between the State andthe Catholic Church. Dom Helvecio was ahead of one of the most important Episcopal Sees of the country in the first decades of the twentieth century, in Mariana/MG, occupying the position during the longest Minas Gerais episcopate, 37 years of government. The thesistries to understand the transformations which the Brazilian Catholic Church pass through since the initiation of the boy Helvecio, held in the first Salesian educational institution established in the country, the school Santa Rosa in Niteroi/RJ, until his achievement to the national episcopate. This work follows his entire trajectory and analyses his actions with the aim to demonstrate the link between individual religious - society, the constant search for the efficiency in the project of neochristianity.